The Three-Decade Cycle of Lithuanian Prose - Sprindytė, Jūratė (Literatūra, 2021)
In the period of 1989-2020 Lithuanian literature experienced a very dynamic literary development. The aim of the article is to highlight specifics of the new cycle and to analyze the prose trends of each decade of regained independence. The author discusses the literary process more synchronically than diachronically. The first period, i.e. the transition from the Soviet regime to the new system, was especially outstanding as the censorship was eliminated, the previously banned works of deportees and resisters were legalized, the postwar émigré writers returned back to culture and opportunities for innovation opened up. The role of writer as a cultural hero diminished. Former writers loyal to the Soviet regime described this situation as crisis, while the younger generation developed postmodernist way of writing. Many works were based on the cultural and historical memory reckoning with the Soviet era. All genres underwent certain transformations, such as emergence of peculiar essay genre, spread of ego-documentaries, revival of short stories, and flourishing popular literature. Serious changes took place after 2004 when Lithuania joined the European Union, which led to economic emigration and encouraged changes in mentality and expanse of local contexts. Mobile, “transit” type of Lithuanian character emerged who changed his place of residence but felt lonely in the global world. This is a huge innovation, bearing in mind the sedentary agrarian Lithuanian culture and the confines of the iron curtain during the Soviet era. Increased quantity of published books decreased their quality.